Study of phase-pure TiO2 for the removal of fluorides in water. (June 2022) - Meier, L.A.; Schvval, A.B.; Ulacco, S.B.; Lorenzetti, A.S.; Vidal, E.; Domini, C.; Morgade, C.I.N.
Abstract: The water resources available worldwide are mainly found in aquifers that are subject to various pollution. The wide variety of possible contaminants suggests materials with nonspecific catalytic activity, among which titanium oxide (TiO2 ) has been extensively investigated. On the other hand, computational chemistry makes it possible to find explanations for experimentally observed results. It is important as a starting point, for a material with such versatility, the study and understanding of the activity of its pure polymorphs in relation to a given pollutant. Since fluoride is an element present in natural water sources which are used for human consumption all over the world, it is essential to use technology that allows its removal to reach concentrations that are not harmful to health. In the present work, the catalytic efficiency of the two most abundant polymorphs of titanium oxide TiO2 is analyzed in a comparative way. The study carried out shows that rutile TiO2 is a good fluoride scavenger unlike anatase TiO2 . Removal is an adsorptive and non-photocatalytic process. The observed behavior could be explained by the differences in the surface of the electric charges between both crystalline phases as well as the different location of the ion in both structures. Graphical Abstract: ga1 Highlights: Anatase TiO2 is not a good remover of fluorides in aqueous solution. Rutile TiO2 efficiently removes fluorides through an adsorption process. Rutile and Anatase polymorphs have different surface charge densities. In Anatase, Fion is preferentially located interstitially. In Rutile the Fion is preferentially adsorbed on Ti atoms from the surface.